Competencies of production in SMEs in assembly industries in a digital, volatile business environment - Hulla, Maria (Array, 2020)
SMEs are currently confronted with major challenges such as increasing uncertainty and volatility. In order to face these challenges, agility and digitalization can be implemented. Both concepts bring about numerous opportunities and new competency requirements. Currently, there are few scientifically based, practical training courses that focus on digitization and/or agility. The aim of this paper is to provide a roadmap for the development of the training concept. In this training, participants will be able to acquire theoretical content on a learning platform in a flexible way and they will be able to apply this knowledge in a learning factory. Based on a literature overview, requirements for such a training and the necessary skills in a digital, volatile business environment will be given.